Molecular Simulation of Oncostatin M and Receptor (OSM–OSMR) Interaction as a Potential Therapeutic Target for Inflammatory Bowel Disease - Du, Qingqing; Qian, Yan; Xue, Weiwei (Frontiers in Molecular Biosciences, 2020)
Therapeutics targeting cytokines such as the oncostatin M (OSM)-mediated inflammation represent a potential strategy for the treatment of inflammatory bowel disease (IBD). Despite the specific role of the interactions between OSM and the receptor (OSMR) has been investigated in IBD pathogenesis, the 3D structure of OSM-OSMR complex remains elusive. In this work, the interaction mode between OSM and OSMR at atomic level was predicted by computational simulation approach. The interaction domain of OSMR was built with homology modeling method. The near-native structure of OSM-OSMR complex was obtained by docking, and long-time scale molecular dynamics (MD) simulation in explicit solvent was further performed to sample the conformations when OSM binds to OSMR. After getting the equilibrated states of the simulation system, per-residue energy contribution was calculated to characterize the important residues for OSM-OSMR complex formation. Based on these important residues, eight residues (OSM: Arg100, Leu103, Phe160 and Gln161; OSMR: Tyr214, Ser223, Asp262 and Trp267) were identified as the “hot spots” through computational alanine mutagenesis analysis and verified by additional MD simulation of R100A (one of the identified “hotspots”) mutant. Moreover, six cavities were detected at OSM-OSMR interface through FTMap analysis and there of them were suggested as important binding sites. The predicted 3D structure of OSM-OSMR complex and the identified “hot spots” constituting the core of the binding interface provide helpful information for understanding OSM-OSMR interactions, and the detected sites serve as promising targets for designing of small molecules to block the interactions.